In vivo measurement of hippocampal GABAA/cBZR density with [18F]-flumazenil PET for the study of disease progression in an animal model of temporal lobe epilepsy. - Lucy Vivash (Public Library of Science (PLoS), 2014)
Purpose Imbalance of inhibitory GABAergic neurotransmission has been proposed to play a role in the pathogenesis of temporal lobe epilepsy (TLE). This study aimed to investigate whether [(18)F]-flumazenil ([(18)F]-FMZ) PET could be used to non-invasively characterise GABAA/central benzodiazepine receptor (GABAA/cBZR) density and affinity in vivo in the post-kainic acid status epilepticus (SE) model of TLE. Methods Dynamic [(18)F]-FMZ -PET scans using a multi-injection protocol were acquired in four male wistar rats for validation of the partial saturation model (PSM). SE was induced in eight male Wistar rats (10 weeks of age) by i.p. injection of kainic acid (7.5-25 mg/kg), while control rats (n = 7) received saline injections. Five weeks post-SE, an anatomic MRI scan was acquired and the following week an [(18)F]-FMZ PET scan (3.6-4.6 nmol). The PET data was co-registered to the MRI and regions of interest drawn on the MRI for selected structures. A PSM was used to derive receptor density and apparent affinity from the [(18)F]-FMZ PET data. Key findings The PSM was found to adequately model [(18)F]-FMZ binding in vivo. There was a significant decrease in hippocampal receptor density in the SE group (p<0.01), accompanied by an increase in apparent affinity (p<0.05) compared to controls. No change in cortical receptor binding was observed. Hippocampal volume reduction and cell loss was only seen in a subset of animals. Histological assessment of hippocampal cell loss was significantly correlated with hippocampal volume measured by MRI (p<0.05), but did not correlate with [(18)F]-FMZ binding. Significance Alterations to hippocampal GABAA/cBZR density and affinity in the post-kainic acid SE model of TLE are detectable in vivo with [(18)F]-FMZ PET and a PSM. These changes are independent from hippocampal cell and volume loss. [(18)F]-FMZ PET is useful for investigating the role that changes GABAA/cBZR density and binding affinity play in the pathogenesis of TLE.